21X-39=13X-23

Simple and best practice solution for 21X-39=13X-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21X-39=13X-23 equation:


Simplifying
21X + -39 = 13X + -23

Reorder the terms:
-39 + 21X = 13X + -23

Reorder the terms:
-39 + 21X = -23 + 13X

Solving
-39 + 21X = -23 + 13X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-13X' to each side of the equation.
-39 + 21X + -13X = -23 + 13X + -13X

Combine like terms: 21X + -13X = 8X
-39 + 8X = -23 + 13X + -13X

Combine like terms: 13X + -13X = 0
-39 + 8X = -23 + 0
-39 + 8X = -23

Add '39' to each side of the equation.
-39 + 39 + 8X = -23 + 39

Combine like terms: -39 + 39 = 0
0 + 8X = -23 + 39
8X = -23 + 39

Combine like terms: -23 + 39 = 16
8X = 16

Divide each side by '8'.
X = 2

Simplifying
X = 2

See similar equations:

| -11X-85=-6X-45 | | 6X-43=3X-22 | | 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 | | 4psquared-12p+7=0 | | 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 | | (9y^2-8y+8)-(3y^2-8y+2)= | | -8b+3+6b=3b+8 | | x*1.618=60 | | 5y-8=-28 | | Y^2+18y+69=0 | | 28+9=2n | | 4x/5x-10=35 | | (3.99)2x+19.99y=111.88 | | 2r+12=6 |

Equations solver categories